A Study And Analysis Of Financial Strength Performance And Liquidity Of Syndicate Bank - RAMSHESH, C.; RAJU, S.ANEEL AMRUTHA (International Journal of Psychosocial Rehabilitation, 2020)
The banking business in India is the backbone of the country’s economy. The Indian banking sector includes cooperative, commercial, nationalised, private, and internationalised banks. The goal of this study is to apply the CAMEL model to analyse the Syndicate Bank’s financial performance. The CAMEL model is a widely used method for evaluating the performance of banking units in the United States and throughout the globe. Outside the subcontinent of India In the United States, the CAMEL rating system was developed to categorise supervisory rating systems.The overall status of the bank This model evaluates the performance of financial institutions (approximately). On all main factors such as capital adequacy, assets, and liquidity, 8,000 entities (primarily banks) were evaluated. The first five components are quality, management efficiency, earning quality, and liquidity, with market risk as the sixth. It was added in 1997. The study is based on secondary data from the annual reports of Syndicate Bank. The data from FIVE years is analysed with the purpose of assessing it by calculating various ratios. Average, standard deviation, coefficient of variation, and other statistical tools, according to the CAMEL rating. A correlation is also calculated. The Syndicate bank’s total capital adequacy level was found. The managerial effectiveness was also excellent. However, the bank’s total earning capacity was excellent. The liquidity position was bad in general.